2013
DOI: 10.1002/bdrc.21033
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐computed tomography imaging and analysis in developmental biology and toxicology

Abstract: Micro-computed tomography (micro-CT) is a high resolution imaging technique that has expanded and strengthened in use since it was last reviewed in this journal in 2004. The technology has expanded to include more detailed analysis of bone, as well as soft tissues, by use of various contrast agents. It is increasingly applied to questions in developmental biology and developmental toxicology. Relatively high-throughput protocols now provide a powerful and efficient means to evaluate embryos and fetuses subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…One of the most important advantages of micro‐CT imaging is that it lends itself to the development of automated skeletal examination. In fact, Wise, Winkelmann, Dogdas, and Bagchi () published work describing methodology to automate skeletal examinations. In addition, Dogdas et al () using a test data set of 167 fetuses, with verified skeletal abnormalities, demonstrated a sensitivity of 0.959 and a specificity of 0.805 for the software program.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important advantages of micro‐CT imaging is that it lends itself to the development of automated skeletal examination. In fact, Wise, Winkelmann, Dogdas, and Bagchi () published work describing methodology to automate skeletal examinations. In addition, Dogdas et al () using a test data set of 167 fetuses, with verified skeletal abnormalities, demonstrated a sensitivity of 0.959 and a specificity of 0.805 for the software program.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous articles have investigated the effects of bone structure, osteogenesis, osteoporosis, bone resorption, bone remodelling, fracture healing, neoplasms and biocompatible materials, 3,7,32,33 within various animal models. The ability of micro-CT to evaluate trabecular structures allows quantification of bone destruction, commonly assessed in drug treatments and oncological progression.…”
Section: Musculoskeletal and Soft Tissuementioning
confidence: 99%
“…It is generally recognized that the assessments of bone density, microarchitecture and strength are significant in skeletal formation/regeneration research field [ 124 ]. In recent years, high-resolution micro-CT has become feasible for in vivo evaluation of bone quality, providing a high possible imaging spatial resolution [ 125 ]. Therefore, a number of research groups concentrate on the application of this advanced technology to appraise bone quality with miRNA treatment.…”
Section: Mirnas and Bone Regenerationmentioning
confidence: 99%